Pengaruh Penyuluhan Menggunakan Media Pop-Up Book Terhadap Pengetahuan Cara Menyikat Gigi Pada Siswa Kelas IV - Maulida, Yunita; Habibah, Siti Sab’atul; Amperawati, Metty; Fansurna, Anderi (Poltekkes Kemenkes Banjarmasin, 2024)
The majority of the Indonesian population has good daily tooth-brushing behavior at 94.7%. However, only 2.8% of them brush their teeth at the correct time at least twice a day, after breakfast and before bed. Lack of dental and oral health knowledge is one of the factors contributing to oral health problems. Dental and oral health knowledge should be imparted at a young age because children begin to comprehend the significance of health and the prohibitions or behaviors that can negatively affect their teeth. Therefore, promoting dental and oral health is necessary. This research aims to determine the effect of counseling using Pop-up Book on knowledge of how to brush teeth in IV class at Madrasah Ibtidaiyah Swasta Iqdamul Ulum Banjar Regency. Quasi-experiment research was employed with a control group pretest-posttest design. The research sample consisted of 47 students using total sampling. The research findings demonstrated that the average knowledge score was 7.92 before counseling using Pop-Up Book and 12.67 after counseling. Paired Sample T-Test results showed that ρ-value 0.000 < α = 0.05, so Ho was rejected and Ha was accepted. This research concludes that counselling using Pop-Up Book has an effect on the students' knowledge of how to brush their teeth in IV class at Madrasah Ibtaiyah Swasta Iqdamul Ulum Banjar Regency. It is recommended that health workers, particularly those in the dental and oral health field, conduct promotional activities for students at Madrasah Ibtidaiyah, including continuous counselling using interesting and not monotonous media to increase students’ knowledge.